Porównanie odnowień sosny zwyczajnej powstałych z siewu i sadzenia w różnych terminach - Barzdajn, Władysław; Kowalkowski, Wojciech; Tomczak, Robert (Leśne Prace Badawcze, 2019)
The aim of this study was to evaluate the practical feasibility of two forest regeneration methods using Scots pine Pinus sylvestris L. To this end, comparative experiments were established in the Złotoryja and Legnica Forest Districts. The site in Złotoryja had been clear cut, while the experimental plot in Legnica was established at a location damaged by wind in 2009 and cleared from wind throws and wind-broken trees before the experiment. Four different dates for sowing and two for planting were chosen in order to investigate the potential forest regeneration with respect to time. Both experiments were established according to the same design: a complete random block design with five replication blocks. To each plot we applied approximately 53 g (1.2 kg/ha) of seeds and planted 230 seedlings (10 200 seedlings/ha). In 2017, the height of the pine trees was recorded and their increment in height was measured in 2016 as well as 2017. A preliminary analysis of results was conducted using ANOVA for multiple experiments in order to identify significant differences and to then combine variables to form homogeneous groups to which the Duncan multiple range test could be applied. For growth traits, the ANOVA showed significant differences between experimental sights as well as a significant interaction of factors with the experimental site. In terms of planting, April was the most advantageous resulting in the greatest tree height in both forest districts, while in the Legnica Forest District the saplings planted in April also showed the greatest annual increments. Among the sowing dates, the most advantageous was the winter sowing, while the April sowing date produced the least desirable results. In conclusion, both sowing and planting are effective methods to establish pine cultures in coniferous forest. Furthermore, both methods may be performed at the currently recommended spring date, but they may also be postponed to summer and winter dates provided favorable weather conditions prevail.